The interlinks between internationalization and sustainability : analysis of an emerging market multinational (2022)
The accelerated dynamism of markets and the grand global challenges are forcing companies to devise different strategies to remain competitive while also contributing to the sustainable development of the societies in which they operate. This challenges companies’ traditional behaviors and capabilities, especially those from emerging markets that operate in uncertain and volatile environments within these economies, forcing them to find alternatives to gain legitimacy among local and international stakeholders in order to remain competitive. In this way, this dissertation aims to analyze the adoption of a sustainability strategy by Emerging Market Multinationals (EMNEs) to safeguard long-term corporate competitiveness and contribute to sustainable development. The research is reported into three papers: a systematic literature review and two empirical papers. The three papers complement one another by identifying the interweaves between firms’ foreign expansion (internationalization), integration of sustainability into corporate strategy, and how both positively contribute to long-term relevance of EMNEs operating in harsh conditions and turbulent environments. The first paper aims to identify previously unexplored aspects of the relationship between corporate sustainability and internationalization in the context of emerging markets. Hence, it provides a systematic review of the literature that connects both concepts. The review included 90 articles published in 61 journals indexed in [Web of Science Core Collection, EBSCO, Scopus and Google Scholar] between 1991 and 2021. The articles were coded into the following categories: publication year, paper title, journal, author name, research objectives, theoretical approaches, geographical and sectorial contexts, methodologies for inquiry, and study findings. A category to classify identified avenues for future research was also included in order to help understand the relationship between internationalization and sustainability. In sum, the systematic literature review concludes that internationalization is a driver for pursuing sustainability initiatives. It also identifies seven broad research streams that connect internationalization and sustainability and suggests avenues for future research. These streams are: (1) Evolution of MNEs and institutional environment in the implementation of sustainability initiatives, (2) Firms’ specific resources and capabilities concerning CSR, (3) The role of networks and supply chains in MNEs, (4) Development of competitive advantages, (5) Geographical and sectorial context, (6) Theoretical Frameworks, and (7) Measures and methods. The second paper presents findings from an empirical study examining the integration of sustainability into an emerging market multinational's corporate strategy. It also considers how such integration might contribute to achieving and maintaining corporate legitimacy and long-term competitive relevance. This study employs a qualitative single case study methodology on a Colombian multinational firm operating in energy transmission, roads, and telecommunication sectors. Primary data were collected using direct observations and 31 technologically mediated face-to-face interviews conducted in five Latin American countries. The study was supported by secondary data such as corporate reports from 2005 to 2021, archival data, and media coverage. The findings suggest that integrating sustainability into corporate strategy enables subsidiaries to respond to internal and external demands successfully. The strategy deployment develops unique firm capabilities that enable subsidiaries to integrate a sustainability focus into the decision-making and initiatives required to overcome the liabilities of operating in volatile, uncertain, and foreign environments. It also allows the firm to gain competitive advantages and safeguard corporate legitimacy. The third paper explains how a corporate sustainability strategy contributes to sustainable development and how it helps in overcoming the liabilities of foreignness. Interviews with elite and non-elite informants, as well as archival data, were used to collect data for this research. According to the findings, firms from emerging markets have adopted the sustainability flag in their internationalization process to overcome liabilities of foreignness and build legitimacy among their stakeholders. It also enables companies to give back to society through their contribution to sustainable development and the creation of public value. Concisely, this dissertation uses a qualitative case study methodology to contribute to the debate on the relationship between internationalization and sustainability in emerging markets by integrating and analyzing previous literature on this field. In addition, we discuss the integration of sustainability into corporate strategy to achieve and maintain corporate legitimacy and long-term competitive relevance. Finally, we analyze the internationalization of EMNEs and the implementation of a sustainability strategy to overcome their liabilities of foreignness and contribute to sustainable development through a single case of a Colombia multinational operating in the energy transmission, roads, and telecommunication sectors. The findings of this thesis contribute to two growing fields of study within International Business: specific characteristics of emerging market firms and their internationalization process, and the incorporation of corporate sustainability in their operations. With regard to policy, this dissertation makes two major contributions. From the outward FDI perspective, emerging market economies should promote and facilitate the incorporation of sustainability strategies to improve international competitiveness of their industries and gain legitimacy abroad, especially when the institutional environment of these countries encourages enterprises to seek growth opportunities abroad. From the inward FDI perspective, governments should partner with multinational firms to achieve sustainable development goals and align corporate sustainability goals with national commitments to the SDGs. These will guarantee the contribution of EMNEs to local and international sustainable development as well as the generation of public value for societies.